La Rousse and the Tapestry Artist: Tracy Chevalier’s Liberation through Images and Colours - Roxanne Barbara Doerr ([sic])
Art has always held a very ambiguous position in human society: on the one hand it has been exploited for promotional use and revered as a stand in for the entity it represents; on the other hand however, its ability to question dogmatic authorities by appealing to an individual’s innermost instincts and thoughts has made it a threatening and seditious force to be reckoned with. As a result, numerous studies on the impact of art and visions on society, authority, and our perception of reality, have emerged and taken many forms of interdisciplinary inquiry (it is sufficient to think of movements such as “literature and the visual arts”, “culture studies”, “cross-cultural image studies” or “law and imagery”, to mention a few). As a confirmation of this, the subversive power of art, in the form of suppressed colours and controversial portraits, is at the heart of two of Tracy Chevalier’s works, The Virgin Blue (1997) and The Lady and the Unicorn (2003). In both novels the protagonists’ lives are dominated by a strong patriarchal society that suppresses the voices of those who do not pertain to politically privileged categories. Art therefore is the force that leads the characters to leave the paths that had been assigned to them by custom and seek out their own future.